Analysis of Criminal Liability Resulting from Seizure of Lost Property - Masood Bassami (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2021)
Iran's civil law allows the finder (lost property) to possess it under certain conditions. However, the question that arises is whether it is a crime if the person who found the property seizes the property. There is disagreement among lawyers about this question. Some believe that illegal seizure is a crime, but there is no consensus on what a criminal offence is. Some believe in theft, some in abuse of confidence, some in the transfer of property of others, and some in the acquisition of property through illegitimate means. On the other hand, some jurists believe that the illegal seizure of property is not a crime. The results of the present study indicate that the opinion of the second group is stronger and seizure of property is not a crime even if it is against the law.